Monograf Sebagai Salah Satu Cara Publikasi Buku Dari Hasil Penelitian - Endang Fatmawati (UIN Sumatera Utara, 2020)
The meaning of monograph is writing on a single subject. The monograph book form is published in one volume or one series. A monograph issue is not a complete issue in several volumes. More precisely not a radiant issue. The monograph book is a straightforward and concise form of writing a research paper with details on a particular subject. Writing a monograph is based on a literature survey, meaning it is the extraction and compilation of relevant information on a single specialized topic. A monograph book is a work of research written by an expert or a specialist in its field and contains one topic or some related subjects. The monograph is provided as a literature reference and can be used to hold learning material. The lecturer and librarian have the opportunity to create a monograph book from research done. Research articles published in journals can be converted into monograph category books so that they are substantially more valuable, have greater material density, and have greater dissemination opportunities.